Disposable labour, passive victim, active threat: Migrant/non-migrant othering in three British television documentaries. (August 2018) - Vickers, Tom; Rutter, Annie
This article analyses discourses about migration within three documentaries that were broadcast on terrestrial British television in January 2014: The Truth about Immigration in the UK and The Hidden World of Britain's Immigrants, both broadcast on BBC Two, and Episode 2 of Benefits Street, broadcast on Channel 4. The methodology involved a detailed analysis of the documentaries, situated within a Marxist analysis of British capitalism, the capitalist crisis, and the economic and political position of migrants. Amidst the contradictions and complexities that were identified within these documentaries, representations of 'migrants' can be grouped into three categories: disposable labour, passive victim, and active threat. We argue these discursive roles reflect and reinforce capitalist exploitation, by constructing 'migrants' as a mutable 'other' to divide the working class.